Dinamika Manajemen Konflik Di Lingkungan Kerja - Didit Darmawan; Rahayu Mardikaningsih; Eli Retnowati; Nurul Masithoh; Ernawati Ernawati (Jurnal of Management and Social Sciences, 2023)
This research addresses the application of conflict management in the work environment. Through analysis, it explores effective resolution strategies and their impact on organizational health. Qualitative research methods were used to collect data from various sources, including interviews, observations, and literature reviews. The study findings show that understanding the concept of conflict and applying appropriate resolution techniques are essential to creating a balanced work environment. Effective constructive solutions involve communication skills training, cultural development, and encouraging active participation to resolve conflicts. The identification of these solutions can have a positive impact on productivity and organizational well-being. Evaluating and measuring the success of conflict management implementation is a key factor to ensure a positive impact. Team performance assessment methods, team member satisfaction surveys, and evaluations were used to gain an understanding of achievements and potential improvements. This research contributes to the understanding of effective conflict management practices in the work environment.